Monitoring Ethylene in Plants: Genetically Encoded Reporters and Biosensors. Issue 8 (11th July 2019) - Fernandez‐Moreno, Josefina‐Patricia; Stepanova, Anna N.
Abstract: Phytohormone ethylene regulates numerous aspects of plant physiology, from fruit ripening to pathogen responses. The molecular basis of ethylene biosynthesis and action has been investigated for over 40 years, and a combination of biochemistry, genetics, cell, and molecular biology have proven successful at uncovering the core machinery of the ethylene pathway. A number of molecular tools have been developed over the years that enable visualization of the sites of ethylene production and response in the plant. Genetically encoded biosensors take advantage of reporter proteins, i.e., fluorescent, luminescent, or colorimetric markers, to highlight the tissues that make, perceive, or respond to the hormone. This review describes the different types of biosensors currently available to the ethylene community and discusses potential new strategies for developing the next generation of genetically encoded ethylene reporters. Abstract : The review describes the different types of reporters and biosensors currently employed by the plant community, compiles information on the available genetically encoded sensors for hormone ethylene, and discusses potential new strategies for developing the next generation of reporters to facilitate the study of ethylene biology in plants.